Green Synthesis of Silver Nanoparticles using Egyptian Date Palm (Phoenix dactylifera L.) Seeds and Their Antibacterial Activity Assessment - Mohamed E Abdel-Alim; Karam Samaan; Dominique Guillaume; Hashim Amla (Bioactivities, 2023)
A simple, cost-effective and eco-friendly synthesis technique of silver nanoparticles (AgNPs) using the aqueous extracts of Egyptian date palm (Phoenix dactylifera L.) seeds and their antibacterial activity assessment have been conducted. Theaqueous extract was used as reducing and stabilizer agents in the synthesis of AgNPs. Characterization of AgNPs was done using different methods including ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared (FTIR), ﬁeld emission-scanning electron microscope (FE-SEM), and X-ray diffraction (XRD). UV-Vis spectrum of the aqueous medium containing AgNPs showed an absorption peak at around 432 nm. FTIR spectra had shown that the biomolecules were responsible for the reduction and capping agents of AgNPs. XRD study showed the particles to be crystalline with a face-centered cubic (fcc) structure. The AgNPs exhibited signiﬁcant anti-bacterial activity against Bacillus subtilis, Escherichia coli, Enterococcus faecalis, and Staphylococcus aureus. Overall, these ﬁndings suggest that biosynthesized AgNPs may be used as a potential therapeutic formulation against bacterial infections.